High-Speed Videography Reveals How Honeybees Can Turn a Spatial Concept Learning Task Into a Simple Discrimination Task by Stereotyped Flight Movements and Sequential Inspection of Pattern Elements - Guiraud, Marie; Roper, Mark; Chittka, Lars (Frontiers in Psychology, 2018)
Honey bees display remarkable visual learning abilities, providing insights regarding visual information processing in a miniature brain. It was recently discovered that bees can solve a task that is generally viewed as spatial concept learning in primates, specifically the concept of ‘above’ and ‘below’. In these works, two pairs of visual stimuli were shown in the two arms of a Y-maze. Each arm displayed a ‘referent’ shape (e.g. a cross, or a horizontal line) and a second geometric shape that appeared either above or below the referent. Bees learning the “concept of aboveness” had to choose the arm of the Y-maze in which a shape – any shape - occurred above the referent, while those learning the “concept of belowness” had to pick the arm in which there was an arbitrary item beneath the referent. Here, we explore the sequential decision-making process that allows bees to solve this task by analyzing their flight trajectories inside the Y-maze. Over 400 hours of high-speed video footage of the bees’ choice strategies were analyzed in detail. With odor cues made unavailable, many bees failed the task, and, with the possible exception of a single forager, bees as a group failed to reach significance in picking the correct arm from the decision chamber of the maze. Of those bees that succeeded in choosing correctly, most required a close-up inspection of the targets. These bees typically employed a close-up scan of only the bottom part of the pattern before taking the decision of landing on a feeder. When rejecting incorrect feeders, they repeatedly scanned the pattern features, but were still, on average, faster at completing the task than the non-leaners. This shows that solving a concept learning task could actually be mediated by turning it into a more manageable discrimination task by some animals, although one individual in this study appeared to have gained the ability (by the end of the training) to solve the task in a manner predicted by concept learning.